Health records for migrants and refugees: A systematic review. Issue 9 (September 2019) - Chiesa, Valentina; Chiarenza, Antonio; Mosca, Davide; Rechel, Bernd
Highlights: The use of Health Records specifically for migrants and refugees improves the quality and continuity of care. Health Records for migrants and refugees have been successfully implemented in several countries, achieving cost-effective results. There is large heterogeneity across countries in the definition and use of Health Records. Better coordination between and within countries is needed. Abstract: Introduction: One of the challenges facing migrants and refugees is access to medical records. The aim of this study was to identify Health Records (HRs) developed specifically for migrants and refugees, describe their characteristics, and discuss their reported strengths and weaknesses. Materials and methods: A systematic review of articles focusing on HRs implemented exclusively for migrants and refugees was undertaken. Publications were identified by searching the scientific databases Embase, Medline, Scopus and Cochrane, the grey literature and by checking the reference lists of articles. Results: The literature search yielded an initial list of 1432 records, with 58 articles remaining after screening of title and abstract. Following full-text screening, 33 articles were retained. Among the 33 articles reviewed, 20 different HRs were identified. Discussion: Our findings suggest that HRs, especially electronic ones, might be efficient and effective tools for registering, monitoring and improving the health of migrants and refugees. However, some of the evidence base is narrative or institutional and needs to be backed up by scientific studies. Conclusions: Health records, implemented specifically for migrants and refugees, seem to have the potential to address some of the challenges that they face in accessing health care, in particular in strategic hotspots, cross-border settings and for migrants on the move.